Silver as a Regulator of Prices (Quarterly Journal of Economics, 1886)
Journal Article Silver as a Regulator of Prices Get access The Quarterly Journal of Economics, Volume 1, Issue 1, October 1886, Pages 81–83, https://doi.org/10.2307/1883110 Published: 01 October 1886